Where did we come from, where are we going? A collective self-criticism and desirable horizons for Organizational Studies in Brazil - Marcio Sá; Rafael Alcadipani; Ariston Azevedo; Ariádne Scalfoni Rigo; Luiz Alex Silva Saraiva (RAE: Revista de Administração de Empresas, 2020)
The following texts, versions of those presented at a free session of the Sixth Brazilian Congress of Organizational Studies (CBEO), view collective self-criticism as essential to the evolution of researchers of Organizational Studies (OS), a field that needs to forge desirable horizons for itself. They also invite peers to reflect on our recent trajectory, in particular on: (1) inheritances, contrasts and demarcations regarding OS’ parent discipline, Administration; (2) a possibility of growth when we are touched by academic virtue; (3) the challenges and propositions which may arise from a recent editorial experience; and, finally, (4) new work directions for a research group to become more effective and articulate in its teaching, research and outreach actions. In the end, an effort at reflective summary is added.